Seroprevalence of Hepatitis Bs antigen among pregnant women visiting primary health care centers in Baghdad Al-Jadeda sector in Baghdad. - Ali, Shayma S.; Salman, Ban A. Ridha (Journal of the Faculty of Medicine Baghdad, 2018)
Background: Hepatitis B is a potentially life-threatening liver infection which is caused by the hepatitis B virus. Universal testing of hepatitis B virus of pregnant women already occurs in many parts of the world, but still suboptimal in resource-limited settings.Objectives: To find the seroprevalence of hepatitis B s antigen in pregnant women visiting primary health care centers in Baghdad Al-Jadeda health sector that belongs to Baghdad Al-Rusafa health directorate and to determine the effect of some social and obstetrical factors in the infected women.Patients and Methods: A retrospective cross-sectional study carried on 6975 records of pregnant women visited primary health care centers from 1st of January 2016 to 30th of June 2017, whose blood samples were tested at the time of visits for hepatitis B s antigen in the reference laboratory and confirmation tests were established in the central public health laboratory in Baghdad for positive cases and included in their records. The effect of certain sociodemographic and obstetrical factors was also assessed in the study.Results:Of total number of 6975 pregnant women records, hepatitis B s antigen was positive for 11, two were excluded to avoid duplication of data and the final number of infected pregnant women was 9 with prevalence rate of 0.13%. No important findings from their antenatal records regarding effect of certain sociodemographic and obstetrical factors were found except that husband of the majority of cases (55.6%) were HBs Ag negative and no information available about rest of the cases (44.4%).Conclusion: There was a low prevalence of hepatitis B among studied pregnant women. We also concluded that source of infection to these women was mainly parenteral rather than sexual.